2009
DOI: 10.7326/0003-4819-151-4-200908180-00007
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review: Elective Induction of Labor Versus Expectant Management of Pregnancy

Abstract: RCTs suggest that elective induction of labor at 41 weeks of gestation and beyond is associated with a decreased risk for cesarean delivery and meconium-stained amniotic fluid. There are concerns about the translation of these findings into actual practice; thus, future studies should examine elective induction of labor in settings where most obstetric care is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
204
5
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(236 citation statements)
references
References 49 publications
19
204
5
8
Order By: Relevance
“…We chose to compare women who underwent IOL at a specific GA to those who were expectantly managed. These findings are consistent with several large cohort studies and a meta-analysis in women without GDM that demonstrated no increase in the CD rate in women with who underwent IOL at term 25,26 .…”
Section: Commentsupporting
confidence: 80%
“…We chose to compare women who underwent IOL at a specific GA to those who were expectantly managed. These findings are consistent with several large cohort studies and a meta-analysis in women without GDM that demonstrated no increase in the CD rate in women with who underwent IOL at term 25,26 .…”
Section: Commentsupporting
confidence: 80%
“…But in a study by Dunne and Colleagues, elective induction was associated with an increased risks of caesarean section when compared with spontaneous onset of labour 16 . A study by Barthelemy revealed 66.9% of vaginal delivery and 29.6% of caesarean section 12 . No maternal morbidities like third and fourth degree tear, PPH, vaginal haematoma were identifi ed in this study though few studies have identifi ed such maternal morbidities.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Barthelemy Tandu-Umba post term pregnancies covered only 14.6% 12 . In a study by John D.Yeast, Angela Jones and Mark Poskins, postdated pregnancy was found to be the most common indication 13 .…”
Section: Discussionmentioning
confidence: 99%
“…This has essentially been spurred by large cohort studies suggesting better neonatal outcomes. 5 We have observed a phenomenon of apparent oxytocin desensitization in patients receiving infusions of oxytocin prior to delivery. At the clinical level, this results in the need for accelerated doses of oxytocin to achieve adequate uterine tone.…”
mentioning
confidence: 99%